Address Forms and Honorifics Encoding in the Fur Society - Jumaa, Abdallah Dawod Omer (Advances in Social Sciences Research Journal, 2019)
Abstract The paper of Address Forms and Honorifics Encoding in the Fur Society is a trial study from the Fur native speaker to shed light on the Fur language and urge the Fur language native speakers to brain storm and reflect on their language to open the gate way to those who are interested in the Fur researches. It is a thorough survey of the address forms and honorifics used in the Fur society. The investigation is a thorough tour in the Fur culture of practicing their social and political relationships using the address terms and honorifics. This is depicted from the familial address forms and honorifics to embrace pre-greeting forms, system of personal names, lexical address forms, honorifics and address terms stem from marital relationships and using the personal pronoun as an address term besides the form hayi to the titles given after professions. Furthermore, the paper explains the titles and honorifics given to the rankings of ruling class and their fillers besides titles given to those who were achieving certain functions in the Sultanate. Key words: the Fur; the Fur language; address forms; honorifics; the Sultanate